(untitled) (Canadian Dermatology Today, 2022)
Atopic dermatitis (AD) is a common inflammatory skin disorder characterized by barrier defect and immune dysfunction. Patients often suffer from severe itch that has a major impact on quality of life. Over 90% of patients report daily itch and over 50% report an impact on sleep patterns. There are numerous related co-morbidities associated with AD including attention-deficit/hyperactivity disorder, depression, anxiety, insomnia, and poor school performance. Part of a successful treatment approach for AD includes patient education and the liberal use of moisturizers (those with ceramides). Additionally, topical corticosteroids and/or non-steroidal agents (such as topical calcineurin inhibitors and phosphodiesterase-4 inhibitors) are mainstays of treatment. For many years, severe atopic dermatitis was treated with the off-label use of phototherapy, methotrexate, cyclosporine, mycophenolate, or azathioprine. The first Health Canada-approved systemic treatment for atopic dermatitis, dupilumab, was approved in 2017. Dupilumab is a recombinant human IgG4 monoclonal antibody that inhibits interleukin-4 (IL-4) and interleukin-13 (IL-13) signaling by specifically binding to the IL-4Rα subunit shared by the IL-4 and IL-13 receptor complexes. Although efficacious and generally well-tolerated, dupilumab can have a slow onset of action and a variable clinical response in some patients. Another monoclonal antibody, tralokinumab, which is a fully human IgG4 monoclonal antibody that specifically binds to the type 2 cytokine IL-13 and inhibits its interaction with the IL-13 receptors, IL-13Rα1 and IL-13Rα2, was approved by Health Canada in October 2021.